Implementing Blockchain Technology in Halal Certification: A Systematic Literature Review of Opportunities and Challenges - Tri Wahyuni; Luqman Hakim Handoko (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Objectives: This study aims to identify trends, key themes, opportunities, and challenges in the application of blockchain technology in halal certification activities. Design/Method/Approach: This study used the Systematic Literature Review (SLR) method with the PRISMA guidelines. Data were collected from Google Scholar using Publish or Perish (PoP). Findings: the research found that blockchain has significant potential to enhance transparency, efficiency, traceability, and accountability in halal certification through features such as smart contracts and decentralized storage. However, significant challenges remain, including infrastructure readiness, human resource limitations, the absence of global standards, and potential ethical gaps. Publication trends indicate an increase in academic interest in this topic. Originality/Value: This research contributes by mapping the latest literature and filling the research gap related to the application of blockchain specifically in halal certification. The results are expected to serve as a scientific and practical foundation for the development of a more credible and sustainable digitalization strategy for the halal industry.